PENDEKATAN KUANTUM DALAM INTEGRASI AGAMA DAN SAINS NIDHAL GUESSOUM - Soleh, Achmad Khudori (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
There are various thoughts on the integration of religion and science, such as the model i‘jâz al-Najjâr, the model of Islamization of al-Faruqi, Ijmâlî Sardar, the Islamic science of Husein Nasr and the universal science of ‘Abd al-Salâm. According to Nidhal, those thoughts still have weaknesses and can not be developed so it needs another alternative. Therefore, Nidhal offers a quantum approach to the integration of religion and modern science. It is based on three principles: non-contradictory principle, layered interpretation principle, falsifiable-theistic principle. The first one is as a basis to integrate religion and science, the next is treated to understand and interpret the sacred text (Qur’an) as the basis of religion, the latest is to ensure the pattern applied in science. Based on these principles, where there is a